2017
DOI: 10.3920/bm2016.0147
|View full text |Cite
|
Sign up to set email alerts
|

Can probiotics enhance vaccine-specific immunity in children and adults?

Abstract: The growing use of probiotics by the general public has heightened the interest in understanding the role of probiotics in promoting health and preventing disease. General practitioners and specialists often receive inquiries from their patients regarding probiotic products and their use to ward off systemic infection or intestinal maladies. Enhanced immune function is among the touted health benefits conferred by probiotics but has not yet been fully established. Results from recent clinical trials in adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…Whether it is beneficial to achieve higher or lower expression of immune-related gene sets is difficult to answer. On the one hand, a strong pro-inflammatory response is generally considered as harmful; on the other hand, a stimulation of the immune response could also have beneficial effects on local and systemic immune regulation [33]. In our earlier report of the FMT trial [11], we described that symptom improvement was found in the allogenic FMT group compared to baseline, which was not the case in the autologous group.…”
Section: Discussionmentioning
confidence: 99%
“…Whether it is beneficial to achieve higher or lower expression of immune-related gene sets is difficult to answer. On the one hand, a strong pro-inflammatory response is generally considered as harmful; on the other hand, a stimulation of the immune response could also have beneficial effects on local and systemic immune regulation [33]. In our earlier report of the FMT trial [11], we described that symptom improvement was found in the allogenic FMT group compared to baseline, which was not the case in the autologous group.…”
Section: Discussionmentioning
confidence: 99%
“…The use of adjuvant prebiotics/probiotics may offer an inexpensive intervention that may contribute to the prevention of influenza following influenza vaccination. However, a high heterogeneity of existing evidence was noted, while there are no reports to date that include children, at least to the best of our knowledge (90,91). Further studies are warranted, particularly in children, to elucidate the effectiveness of probiotics in the prevention of influenza and decide on the optimal strains, dose, and the timing and duration of supplementation, since there are many strains of probiotics with established immune modulatory effects yet to be tried.…”
Section: Probiotics and Influenza In Childhoodmentioning
confidence: 97%
“…Об иммуностимулирующей и иммуномодулирующей функции бактериальных адъювантов свидетельствует повышение титра антител, возрастание активности Тц-и/или Тх-клеток после их введения. Опубликован ряд работ, показывающих адъювантное действие пробиотических бактерий лактобацилл и бифидобактерий при противовирусной, а также противострептококковой вакцинации [27]. В последние годы идентифицированы бактериальные адъюванты на основе молочнокислых бактерий, компоненты бактериальной стенки, фибронектин, связывающий белок 1 Streptococcus pyogenes, поверхностные флагеллины, которые способны индуцировать антительные ответы.…”
Section: рис 1 классификация M Tuberculosis на различные линии и сunclassified